Actualizing children's participation in the development of outdoor play areas at an early childhood institution. Issue 3 (September 2016) - Nah, Kwi-Ok; Lee, Sun-Mi
This study examined how children's participation can be actualized, and their perspectives respected, through an action research project that engaged them in the development of an outdoor play area in a child care center in South Korea. An educator devised a broad plan and invited children to participate and take the initiative in leading the project. Young children were capable of expressing their points of view and could contribute directly to issues that mattered to them if they worked in accordance with "child-centered" methods and were appropriately supported by adults. Communication with children was also identified as an important means of clarifying their true perspectives, also allowed for the formation of shared meanings. The children perceived themselves as confident learners, developed the ability to communicate and negotiate with other children and adults, showed initiative and enthusiasm, and acquired democratic attitudes and skills. The educator also changed her perspectives and attitudes toward children's rights and capacities as well as toward outdoor play and learning and maintained these changes in her pedagogy and management of the classroom. An inclusive context and sustainable implementation of child participation are recommended for the purpose of realizing children's rights and transforming education and child care practices.